Morpho-Physiological Effects of Salt Stress on Germination and Early Seedling Development in Okra (Abelmoschus esculentus L. cv. Toros Sultanı) - Yücel, Yusuf Cem; Firdes Ulas; Haji Nour, Sa Ad Mohamed; Ulas, Abdullah (Annals of Arid Zone, 2025)
Okra (Abelmoschus esculentus L.) is a vegetable crop known for its high nutritional value and increasing economic importance, particularly due to its adaptability to warm climate conditions. However, salinity - one of the widespread abiotic stress factors affecting agricultural lands - negatively impacts the germination and seedling development of many cultivated species, including okra. This study was conducted in 2024 at the Department of Soil Science and Plant Nutrition, Faculty of Agriculture, Erciyes University, with the objective of evaluating the effects of daily irrigation with water of different salt concentrations (0, 4, 8 and 12 dSm-1) on the germination and early seedling development of the okra cultivar ‘Toros Sultanı’. In the experiment, 50 seeds were used per treatment with five replications. A comprehensive data set consisting of 29 morpho-physiological parameters related to germination and germination matrix was measured. The results revealed that all salt treatments had statistically significant effects (p < 0.001) on all measured germination and seedling parameters. While limited reductions or signs of metabolic adaptation were observed at 4 and 8 dSm-1, the 12 dSm-1 treatment caused marked declines in several critical traits such as germination percentage, germination speed, vigor indices, root-to-shoot ratio, Timson and modified Timson indices, synchronization and emergence indices. The stress tolerance index (STI) calculations showed that the ‘Toros Sultanı’ cultivar exhibited physiological tolerance under moderate salinity but that this tolerance diminished considerably under high salinity conditions like 12 dSm-1. These findings suggest that the ‘Toros Sultanı’ cultivar holds agronomic potential for production in saline environments up to 8 dSm-1, while higher salinity levels may lead to substantial yield and emergence losses. The data generated from this study contribute to the understanding of varietal- and species level adaptation mechanisms to salt stress and offer a scientific basis for future research focused on the management of saline soils.